Stump grafting old citrus: Navel orange scions set fruit in fifth growing season following grafting to stumps old old seedling trees - R LaRue (California Agriculture, 1953)
After four growing seasons, thriving scions grafted into old seedling orange tree stumps demonstrated a way to rehabilitate orchards where the original variety is no longer profitable.